2013
DOI: 10.21608/jpp.2013.74210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chicken Manure Combined With Bio-Fertilizers, Mineral Fertilizer and Some Foliar Applications On: 1- Vegetative Growth and Some Chemical Constituents of Tomato Leaves.

Abstract: Two successive field experiments were conducted in a private farm at Gemiana village near El-Mansoura city, Dakahlia Government, Egypt, during seasons of 2009 and 2010 to evaluate the effect of two rates of chicken manure combined with bio-fertilizers, mineral fertilizers and some foliar application treatments as well as their interactions on vegetative growth parameters (Plant height, No. of branches/plant, No. of leaves/plant, Fresh and Dry weights)and some chemical constitutes of tomato leaves (Lycopersicon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
(5 reference statements)
2
6
0
Order By: Relevance
“…At PU65 (N: 44.04 %) the leaf area reduced but was higher than the control. This effect of nitrogen on increasing leaf area of tomato plants was also observed by authors [42][43][44].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…At PU65 (N: 44.04 %) the leaf area reduced but was higher than the control. This effect of nitrogen on increasing leaf area of tomato plants was also observed by authors [42][43][44].…”
Section: Resultssupporting
confidence: 86%
“…The greatest number of flowers per plant was observed when the tomato plants were fertilized with PU50 (N: 34.1 %) while the lowest number of flowers was observed when the plants were fertilized with PU65 (N: 44.04 %) ( Figure 11). Authors [40][41][42][43][44][45][46][47] reported that tomato plants treated with nitrogen fertilizer produced higher number of flowers than the control plants. The increase flower numbers might be due to increased content of available nitrogen which promotes better vegetative growth and enhances flower of tomatoes.…”
Section: Resultsmentioning
confidence: 99%
“…According to Akanbi et al [23], a combined application of 4 t/ha maize straw compost and N mineral fertilizer at 30 kg/ha increased plant growth and gave higher tomato yield. Dawa et al [24] discovered that fertilizing tomato plants with mixed fertilizers chicken manure at 6 ton/fed with 50% NPK from the recommended dose, i.e., 75 O kg/fed and sprayed with seaweed extract at a rate of 2.5 mL/L produced the highest values of vegetable growth parameters, chlorophyll, N, P, and K percentages in tomato leaves. Pepper chicken manure as organic fertilizers) in the presence of biofertilizers enhanced vegetative plant growth and NPK percentages in leaves [25].…”
Section: Lycopersicon Esculentum Miller) Arementioning
confidence: 99%
“…The increase in tomato plant height might be attributed to hormone components such as cytokinins and auxins in SLF and nitrogen in PU50, which promote plant height. [24,25] discovered that foliar application of seaweed extract with chicken manure as a source of organic fertilizer and in the presence of biofertilizers increased vegetative plant development and N, P, and K percentages in leaves on pepper and tomato plants.…”
Section: Preparation Of Mixed Fertilizer (Slf+pu50)mentioning
confidence: 99%
“…Application of organic fertilizers is very important for providing the plants with their nutritional requirements without having any undesirable impacts on the environment (Patil et al 2004, Bayoumi 2005, Fawzy et al, 2007, and Dawa et al 2013. Inoculation of tomato seedlings twice with biofertilizer "microbein" with nitrogen fertilizer at the rate of 100-120 Kg N/fed combined with compost at the rate of 8 t./fed recorded the highest values of total fruit yield of tomato grown in clayey loam to sandy soils (El-Tohamy et al 2009, Ahmed et al 2013and Mesallam et al 2017.…”
Section: Introductionmentioning
confidence: 99%